PacBio Single-Molecule Long-Read Sequencing Reveals Genes Tolerating Manganese Stress in Schima superba Saplings - Liaquat, Fiza; Munis, Muhammad Farooq Hussain; Arif, Samiah; Haroon, Urooj; Shi, Jianxin; Saqib, Saddam; Zaman, Wajid; Che, Shengquan; Liu, Qunlu (Frontiers in Genetics, 2021)
Schima superba (Theaceae) is a subtropical evergreen tree and is used widely for forest firebreaks and gardening. It is a plant that tolerates salt and typically accumulates elevated amounts of Manganese in the leaves. With large ecological amplitude, this tree species grows quickly. Due to its substantial biomass, it has a great potential for soil remediation. To evaluate the thorough framework of the mRNA, we employed PacBio sequencing technology for the first time to generate S. Superba transcriptome. In this analysis, overall, 511,759 full length non chimeric reads were acquired, and 163,834 high-quality full-length reads were obtained. Overall, 93,362 open reading frames were obtained; of which 78,255 were complete. In gene annotation analyses, the Kyoto encyclopedia of genes and genomes (KEGG), Clusters of orthologous genes (COG), Gene ontology (GO) and Non-redundant (Nr) databases were allocated 91,082, 71,839, 38,914 and 38,376 transcripts, respectively. To identify long noncoding RNAs (lncRNAs) we utilized four computational methods associated with Protein families (Pfam), Cooperative data classification (CPC), Coding assessing potential tool (CPAT) and Coding non coding index (CNCI) databases and observed 8,551, 9,174, 20,720 and 18,669 lncRNAs respectively. Moreover, nine genes were randomly selected for the expression analysis, which showed highest expression of Gene 6 (Na_Ca_ex gene), and CAX (CAX-interacting protein 4) was higher in Manganese (Mn) treated group. This work provided significant number of full-length transcripts and refined the annotation of the reference genome, which will ease advance genetic analyses of S. superba.